Evaluation Opportunities tor Recreational Sport Services – Adapted to Higher Education Environment - Pfau, Christa; Bács, Zoltán; Fenyves, Veronika; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2018)
In our study, we analyse various researches dealing with quality aspects of sport services, and different quality models related to the interpretation of quality. The results which were obtained in the framework of primary research activity present the opinions of students from five different research universities. Sport services’ operation and sustainability are determined by market regulations, as parts of the service industry. Considering that the university leisure sports services take place in a competitive environment, the universities often have to compete with external sports service providers for achieving confidence of the young generations. For the qualitative tests, we used the QSport-14 measurement scale, which is generally applied by sports centres. This scale investigates the sports services according to three different aspects: (1) instructors, (2) infrastructural facilities and equipment and (3) offered sport programs. We have adapted the measurement scale to the university environment because of the differences and special characteristics of external sports service providers and university sports services. In addition, we analysed the factors influencing recreational sports, and we also examined that what changes would be needed in order to improve the quality of recreational sport activities in higher education.